The Self-Healing Performance of Carbon-Based Nanomaterials Modified Asphalt Binders Based on Molecular Dynamics Simulations - Gong, Yan; Xu, Jian; Yan, Er-hu; Cai, Jun-hua (Frontiers in Materials, 2021)
In this study, the molecular dynamics simulation was used to explore the effects of carbon-based nanomaterials as binder modifiers on self-healing capability of asphalt binder, and to investigate the microscopic self-healing process of modified asphalt binders under different temperature. An asphalt average molecular structure model of PEN70 asphalt binder was constructed firstly. Further, three kinds of carbon-based nanomaterials were added at three different percentages ranging from 0.5% to 1.5% to the base binder to study their effects on the self-healing capability, including two carbon nanotubes (CNT1 and CNT2) and graphene nanoflakes (GNF). Combining with the three-dimensional (3D) micro-crack model to simulate the asphalt self-healing process, the density analysis, relative concentration analysis along OZ direction, and mean square displacement analysis (MSD) were performed to investigate the temperature sensitive self-healing characters. Results showed that the additions of CNTs were effective in enhancing the self-healing efficiency of the plain asphalt binder. By adding 0.5% CNT1 and 0.5% CNT2, about 652% and 230% of the MSD of plain asphalt binder was enhanced at the optimal temperatures. However, the use of GNF as an asphalt modifier did not provide any noticeable changes on the self-healing efficiency. It can be found that the self-healing capability of the asphalt was closely related to the temperature. For base asphalt, the self-healing effect became especially high at the phase transition temperature range. While for the modified asphalt, the enhancement of the self-healing capability at the low phase transition temperature (15 °C) became negligible. In general, the optimal healing temperature range of the CNTs modified asphalt binders is determined as 45–55 °C and the optimal dosage of the CNTs is about 0.5% over the total weight of the asphalt binder. Considering the effect of carbon-based nanomaterials on the self-healing properties, the recommended carbon-based nanomaterials modifier is CNT1 with the aspect ratio of 1.81.